STRATEGY FOR RESUMING ELECTIVE SURGICAL PROCEDURES DURING & AFTER COVID-19 PANDEMIC - Shabir Ahmed Lehri; Khan, Muhammad Iqbal; Riffat Arbab (Journal of University Medical & Dental College, 2021)
ABSTRACT COVID-19 pandemic has afflicted the individuals, national economies, and healthcare system worldwide. It has badly struck the ongoing and planned surgical procedures in nearly all healthcare centers which has led the surgical procedures to come to a grinding halt. This serious issue invites comments from surgical experts throughout the world.